2017
DOI: 10.1016/s0140-6736(16)31403-9
|View full text |Cite
|
Sign up to set email alerts
|

Masitinib for treatment of severely symptomatic indolent systemic mastocytosis: a randomised, placebo-controlled, phase 3 study

Abstract: Summary Background Indolent systemic mastocytosis, including the subvariant of smouldering systemic mastocytosis, is a lifelong condition associated with reduced quality of life. Masitinib inhibits KIT and LYN kinases that are involved in indolent systemic mastocytosis pathogenesis. We aimed to assess safety and efficacy of masitinib versus placebo in severely symptomatic patients who were unresponsive to optimal symptomatic treatments. Methods In this randomised, double-blind, placebo-controlled, phase 3 s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 28 publications
3
52
0
Order By: Relevance
“…Pre-clinical studies using anti-c-kit antibodies [ 40 ], anti-TNF-α antibodies [ 41 ], or the mast cells stabilizer disodium cromoglycate (cromolyn) [ 42 ] have demonstrated promising results in mouse models. Masatinib is a tyrosine kinase inhibitor that targets c-kit receptors and is clinically developed and approved for treatment of recurrent or unresectable grade III dog mast cell tumors and is the first approved anticancer drug in veterinary medicine [ 43 ]. Masatinib has been translated to human clinical trials for its evaluation in gastro intestinal stromal tumor (GIST), mastocytosis and pancreatic cancer [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical studies using anti-c-kit antibodies [ 40 ], anti-TNF-α antibodies [ 41 ], or the mast cells stabilizer disodium cromoglycate (cromolyn) [ 42 ] have demonstrated promising results in mouse models. Masatinib is a tyrosine kinase inhibitor that targets c-kit receptors and is clinically developed and approved for treatment of recurrent or unresectable grade III dog mast cell tumors and is the first approved anticancer drug in veterinary medicine [ 43 ]. Masatinib has been translated to human clinical trials for its evaluation in gastro intestinal stromal tumor (GIST), mastocytosis and pancreatic cancer [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various TKIs have been investigated for therapeutic use against mastocytosis. Imatinib and masitinib mesylate show efficacy for patients with wild-type KIT mast cell neoplasia (Lortholary et al, 2017).…”
Section: Treatment Of Mastocytosismentioning
confidence: 99%
“…These receptors synergistically signal proliferation and migration of cancer and hematopoietic cells, including macrophages. By targeting c-Kit, Lyn, and Fyn, masitinib is particularly efficient in controlling the survival, differentiation, and degranulation of mast cells and, thus, modulating the mast cell-induced array of proinflammatory and vasoactive effects (25,28). Accordingly, clinical trials have shown therapeutic effects of masitinib in cases of mastocytosis, a rare disease characterized by abnormal accumulation and activation of mast cells in various tissues and organs (28).…”
Section: Introductionmentioning
confidence: 99%
“…By targeting c-Kit, Lyn, and Fyn, masitinib is particularly efficient in controlling the survival, differentiation, and degranulation of mast cells and, thus, modulating the mast cell-induced array of proinflammatory and vasoactive effects (25,28). Accordingly, clinical trials have shown therapeutic effects of masitinib in cases of mastocytosis, a rare disease characterized by abnormal accumulation and activation of mast cells in various tissues and organs (28). Masitinib was also shown to beneficially modulate CNS function in multiple sclerosis (29), stroke (30), and Alzheimer' s disease (31).…”
Section: Introductionmentioning
confidence: 99%